Ethnicity and social work practice - Cox, Carole B.; Ephross, Paul H. (New York ; Oxford : Oxford University Press, 1998)
The authors offer a broad conceptual model of ethnic identity which enables social workers to practise effectively with clients of all ethnic and racial groups. They address all areas of practice (individuals, families, groups, and communities) and include chapters on social services, health care, & social planning and policy development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social work with minorities -- United States; Ethnic groups -- United States; Ethnicity -- United States